Pendidikan Toleransi Menurut QS Al-Baqarah Ayat 256 Perspektif Ibnu Katsir - Iqbal Amar Muzaki (Wahana Karya Ilmiah Pendidikan, 2021)
This writing presents an analysis of tolerance education as contained in QS Al-Baqarah verse 256 Ibn Kathir's perspective. Ibn Kathir was a well-known scholar who produced many works. Tafsir ibn Kathir is one of his monumental works. This study uses a qualitative approach to the form of analysis of the work of Ibn Kathir. The author concludes that the substance of tolerance is to provide opportunities for other individuals to sincerely believe in their religion without coercion from others. This mindset must be instilled through education. If this mindset is embedded in the minds of the people, then the hope of a conducive and peaceful life will be realized